Acidente Isquémico Transitório e Angiopatia Amiloide Cerebral Associada a Inflamação: Apresentação Semelhante, Entidades Diferentes - Oliveira, Raquel; Batista, Raquel; Flores, Priscila; Massano, Ana; Galo, Sérgio; Martins, Isabel (Sinapse, 2024)
Cerebral amyloid angiopathy-related inflammation (CAA-ri) is a rare subtype of CAA characterized by a perivascular inflammatory response to amyloid deposition in the brain. The authors detail the case of a 74-year-old man with aphasia, who was diagnosed with probable CAA-ri following brain magnetic resonance imaging. Treatment recom- mendations included a 5-day course of high-dose methylprednisolone. CAA-ri may manifest with transient or permanent neurological symptoms resem- bling a transient ischemic attack or stroke, potentially leading to misdiagnosis and inadequate long-term treatment. Hence, our objective is to highlight the clinical and imaging findings of this case.